Business improvement districts, class turf war and the strategic weaponisation of class monopoly rent. (February 2023) - Anderson, Matthew; Arms, Zachary
Business improvement districts (BIDs) are understood as a proactive response by locally dependent property owners and businesses aimed at attracting capital investment and consumers back to the central city at a time of increasingly gutted public sector resources. BIDs have yet to be explicitly examined as a form of rent-seeking, even though the primary motivation for property owners to self-impose additional taxes for implementing 'clean and safe' programmes is rent. In this context, the self-imposed tax is treated as a speculative investment that will hopefully yield a return in the form of enhanced profit for businesses and rents for landowners. As such, we conceptualise BIDs as not only a form of rent-seeking, but an alliance of private-sector actors engaged in the collaborative and strategic mobilisation of class monopoly rent as a weapon against all perceived barriers to profitability. Based on evidence from Seattle, Washington, the paper deepens our understanding of BIDs by linking this phenomenon to the spatial dynamics of rent within the contemporary neoliberal city and concludes by discussing the implications for what BIDs reveal about class monopoly rent in particular, the kind of class conflict this form of rent configures and its role within wider processes of neoliberal urbanisation.